(untitled) (Journal of Engineering, 2013)
Over the last few years, there has been a worldwide increase in the use of composite materials for rehabilitation of deficient reinforced concrete structures. One important application of this technology is the use of Carbon Fiber Reinforced Polymer (CFRP) jacket to provide external confinement of reinforced concrete columns. Square concrete column specimens 100×100×1000 mm with concrete compressive strength of about 30 and 50 MPa, steel fiber volume fraction 0%, 0.5%, 0.75%, and percentage of longitudinal reinforcement 2.01%, 3.14% and 4.52% were tested until failure in previous research. In this research seven tested columns were repaired and rehabilitated using one layer of CFRP flexible wraps and tested to determine their ultimate load carrying capacity. A comparison between the behavior of column specimens before rehabilitation and after rehabilitation was carried out. The result show that high strength concrete (HSC) columns show reduction in the maximum load carrying capacity of about 2% - 21%, while the deflection at maximum load significantly increases relative to concrete columns before rehabilitation.